Pawai Malam Lebaran Menggunakan Musik DJ di Perbaungan Kabupaten Serdang: Perspektif Tokoh Muhammadiyah dan Al-Washliyah - Damanik, Deniansyah; Arifin, Oji (UIN Sunan Kalijaga Yogyakarta, 2022)
Every 1st night of Shawwal (Eid al-fithr of Muslims) in Perbaungan District, Serdang Bedagai Regency, North Sumatra, there have been a takbir parade with decorative cars and DJ music. Therefore, the author is interested in examining this problem from the perspective of Muhammadiyah and Al-Washliyah figures in Perbaungan District. This article is field research methods by conducting interviews to some religious figures in Perbaungan district. This article found that the event organizers forbid the use of DJ music in the regulation. Apart from that, the opinion of the Perbaungan District Muhammadiyah figures tends to prohibit this act due to the mixing of takbir with DJ music. this is inversely proportional to the figure of Al-Washliyah Perbaungan who still has the opportunity to allow it because there is no firmly argument (qoth'i) which prohibits music and as long as it is not negligent the listener. This article finds that the opinion of Al-Washliyah figures is more relevant and easily accepted by the public. This is because the banning of a tradition requires a lot of time. In Islamic law, the principle of tadarruj is known, which means the prohibition or order of something must be done in stages.